Psychometric Validation of a General Health Quality of Life Tool for Cats Used to Compare Healthy Cats and Cats with Chronic Kidney Disease. (14th November 2015) - Bijsmans, E.S.; Jepson, R.E.; Syme, H.M.; Elliott, J.; Niessen, S.J.M.
Abstract : Background: Numerous validated psychometric tools are available to assess impact of disease on a human's quality of life (QoL). To date, no psychometrically validated general health‐related QoL tool exists for cats. Hypothesis/Objectives: To develop and validate a tool for assessment of owner‐perceived QoL in cats (CatQoL) and to use this tool to compare QoL between healthy cats and those with chronic kidney disease (CKD). Animals/Subjects: Total of 204 owners of young healthy cats (YH, n = 99; <9 years), older healthy cats (OH, n = 35), and cats diagnosed with CKD (CKD, n = 70) completed the CatQoL. Methods: Discussions with a focus group and 2 pilot surveys informed design of 16 QoL questions grouped into 4 domains. Each item scored according to frequency and importance, and item‐weighted‐impact‐scores were calculated. The validity of the tool was assessed using principal components analysis and Cronbach's α. The average item‐weighted‐impact‐score (AWIS) was compared among groups and domains. Results: Sixteen‐item CatQoL showed good internal consistency reliability (Cronbach's α, 0.77) and unidimensionality with significant loadings (0.2–0.7) and communalities (>0.3). Young healthy cats had significantly higher AWIS (median [IQR], 1.25 [0.63, 1.88]) than OH (0.56 [−0.06, 1.00]) and CKD cats (−0.06 [−0.81, 0.88]), P < .001). CKD cats had significantly lower AWIS for eating domain (YH: 2.00 [1.00, 3.00]; OH: 2.00 [0.67, 3.00]; CKD : 1.00 [0.00, 2.67]) when compared with the YH group and OH group, and all groups differed significantly in their management domain (YH: −0.50 [−1.00, 0.00]; OH: −1.00 [−1.88, −0.50]; CKD : −1.50 [−2.50, −1.00], P < .001). Conclusions and Clinical Importance: The CatQoL was validated for use in cats, and can be used as additional assessment parameter in clinical and research settings.